Is Environmental Protection Beneficial for the Environment?. Issue 3 (29th May 2016) - Ansuategi, Alberto; Marsiglio, Simone
Abstract: We analyze a simple endogenous growth model with environmental interactions. Economic production generates emissions of pollutants whose environmental impact is mitigated by abatement activities financed by government expenditure; environmental quality affects preferences but does not play any productive role. We show that government intervention, by reallocating resources from capital accumulation to environmental preservation activities, allows the economy to achieve a sustainable balanced growth path. Along such a path, softer environmental policy regimes lead to win–win outcomes, fostering economic growth and improving environmental quality. Such a result needs to be interpreted as a long run outcome, but it clearly shows that the compatibility between economic growth and environmental improvement is far from automatic. Indeed, in the long run it could paradoxically be the case that both the economy and the environment benefit from low levels of environmental protection.